Job Burnout and Employee Performance in Hospitality Industry: The Role of Social Capital - Dhyah Harjanti (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2019)
The hospitality industry is known for its labor-intensive and intense interpersonal relationships characteristic. The high rate of burnout in hospitality industry has been a crucial issue. The burnout could lead to employee performance decline. The previous studies suggested that the happy and cooperative employees tend to deliver a better performance. Since cooperative is a part of social capital, this study aims to analyse the role social capital in reducing burnout and improving employee performance.The data collection was conducted by distributing questionnaires to all of non-daily worker employees at the first-line and middle-line level in three budget hotels in the similar chained hotel group in Surabaya. We processed the data using partial least square analysis technique.The result reveals that the social capital have a significant negative influence on burnout, and a significant positive influence on employee performance. We also ascertain that burnout have a significant negative influence on employee performance.